A novel PU/PVA-co-PE composite nanofiber membrane for water filtration. (October 2019) - Li, Mufang; Wu, Yongzhi; Zhong, Weibing; Zhao, Qinghua; Guo, Qihao; Liu, Ke; Liu, Qiongzhen; Wang, Yuedan; Lu, Zhentan; Wang, Dong
Filter membranes with high efficiency and low energy consumption are gaining more attention owing to the increase in water pollution. To enhance the filtration performance, a novel spindle polyurethane (PU) / poly(vinyl alcoholco-ethylene) (PVA-co-PE) composite nanofiber membrane was prepared. It is the first time that the spindle composite nanofibers and nanofiber membranes are prepared based on the PU/PVA-co-PE/CAB (cellulose acetate butyrate) immiscible polymer blends. The effects of PU concentration on the morphology, size distribution, and hydrophilicity of PU/PVA-co-PE nanofiber membranes were analyzed. The pure PVA-co-PE nanofiber membrane and PU/PVA-co-PE composite nanofiber membranes were used to filtrate the nanoparticle suspension with scarlet pigments (50–300 nm). Due to the smaller pore size, looser structure, and larger porosity, the rejection rate and flux of spindle PU/PVA-co-PE composite nanofiber membranes are both higher than that of pure PVA-co-PE nanofiber membrane. When the basic weight of nanofiber layer is 6 g/m 2, the rejection rate of all the PU/PVA-co-PE membranes are above 99%. This study provided a novel, facile, and high-throughput method to prepare spindle nanofiber membranes and indicated the advantage of spindle PU/PVA-co-PE composite nanofiber membranes in the application of water filtration.